A qualitative exploration of factors influencing bullying behavior in schools - Dini Mulyati; Suraya Putri; Eri Riana Pertiwi; Ratna Juwita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Bullying in schools is a growing global problem that affects victims, perpetrators, and the surrounding environment. Environmental and individual factors, such as family, mass media, and social pressure, play a significant role in the emergence of bullying behavior. In Indonesia, this phenomenon is still often overlooked, even though it has long-term consequences for students' psychological and academic well-being. Purpose: To analyze the factors that contribute to bullying behavior in schools. Method: A descriptive qualitative design with an exploratory focus was conducted in April 2025 at State Vocational High School 1 Banda Aceh. A total sampling technique was utilized, resulting in the selection of four participants, consisting of key informants including teachers and the headmaster. Data collection was carried out through triangulation, integrating multiple data sources, methods, and theoretical perspectives to enhance the credibility and validity of the findings. In-depth interviews served as the primary data collection method. The collected data were analyzed using thematic analysis, allowing for the identification of recurring patterns and the extraction of core meanings from the participants' narratives. Results: Bullying behavior among students is influenced by family, media, and peer environments. A lack of support or harsh treatment at home can lead children to imitate negative behavior at school, while exposure to violent media and poor parental supervision further contribute to aggression. Peer pressure also plays a significant role, as teenagers often follow group behavior to feel accepted. Conclusion: Preventing bullying requires a comprehensive approach involving families, schools and communities.